INDUSTRIAL ECOLOGY AND LEGISLATION OF THE ECOLOGICAL APPROACH TO PRODUCTION IN THE COUNTRIES IN TRANSITION AND THE EU - Vuković, Veljko; Ivic, Mladen; Vuković, Miljana (Journal of process management and new technologies, 2017)
It is on the way of producing that how many resources and how much energy we would spend, how many harmful substances would appear in the environment, as well as how the life cycle of a product would be like depends. Through certain interventions in the production process we can have a favorable impact on all these parameters. By using higher quality materials we have a direct impact on quality and longer life cycle of the product, by using a better technology we reduce the consumption of energy and resources, by a better and more efficient design we have an impact on the energy consumption throughout life cycle of the product, and by all of the aforementioned things we contribute to less pollution and sustainability of our environment. Therefore, it is quite clear that today the industrial ecology is one of the most significant aspects of the production issues in the Republic of Srpska and the EU.